A fuzzy logic model for biogas generation in bioreactor landfills. Issue 2 (1st November 2013) - Abdallah, Mohamed; Fernandes, Leta; Rendra, Septa; Warith, Mostafa
Abstract : A fuzzy logic model was developed to simulate the effect of leachate recirculation and sludge addition on the biogas generation in anaerobic bioreactor landfills. The model was designed using a fuzzy logic system (FLS) which incorporated 3 input variables (time, leachate recirculation, and sludge addition) and a single manipulated output (biogas generation rate). The biogas production rate was measured during the experiment and was increasing proportionally with the rate of both leachate recirculation and sludge addition. The experimental work involved the operation of six simulated laboratory-scale bioreactors for over a year under different operating schemes. The experimental results were employed in formulating the fuzzy rule base, calibrating the model, and verifying its predictions. Then, the model was validated against other measured data that was compiled from published studies. The FLS model simulations demonstrated high correlation with the experimental observations.